CTD profiles of the pockmarks Chez-le-Bart (CB), Treytel 3 (TR3) and Treytel 2 (TR2) and La Lance (LL) in Lake Neuchatel, Switzerland in 2017 - Wirth, Stefanie B; Bouffard, Damien; Zopfi, Jakob (PANGAEA, 2020)
CTD profiles through the water column and into the pockmark chimneys were realized using a RBR probe equipped with additional weight underneath (15 kg as Pb cubes).
Keywords: chimney; Karst; Lake Neuchatel; LGD lacustrine groundwater discharge; Pockmark; ROV remotely operated vehicle; sediment fluidization; SGD submarine groundwater discharge